Gamification Teaching Technique During the Pandemic: A Review - Mohd Iftitah Jamil; Firdaus Kamaruddin; Mohamad Norfi Ramli; Zulhilmi Khatam (Multidisciplinary Applied Research and Innovation, 2023)
This paper is related to a study conducted to look at the growing learning process either within or outside the country, namely Game Based Learning techniques that are increasingly applied during pandemic situations around the world. GBL technique that practice gamification technique in the learning process are described in detail to make it easier for teachers and students to better understand what GBL is. In pandemic situations where students are unable to follow the learning process physically, the use of this GBL can be practiced to replace traditional teaching technique which is reliance on papers and books. This study which uses non empirical method on one type of learning game that is Minecraft Education Edition will be observed through personal observation method. By using the MDA framework and also the game experience application, the results of using this GBL technique will be seen how it functions whether it helps or not in the learning process